Peroxisomal alterations in Alzheimer’s disease - Kou, Jianqiu; Kovacs, Gabor G.; Höftberger, Romana; Kulik, Willem; Brodde, Alexander; Forss-Petter, Sonja; Hönigschnabl, Selma; Gleiss, Andreas; Brügger, Britta; Wanders, Ronald; Just, Wilhelm; Budka, Herbert; et al. (Acta neuropathologica, 2011)
In Alzheimer’s disease (AD), lipid alterations are present early during disease progression. As some of these alterations point towards a peroxisomal dysfunction, we investigated peroxisomes in human postmortem brains obtained from the cohort-based, longitudinal Vienna-Transdanube Aging (VITA) study. Based on the neuropathological Braak staging for AD on one hemisphere, the patients were grouped into three cohorts of increasing severity (stages I-II, III-IV, and V-VI, respectively). Lipid analyses of cortical regions from the other hemisphere revealed accumulation of C22:0 and very long-chain fatty acids (VLCFA, C24:0 and C26:0), all substrates for peroxisomal β-oxidation, in cases with stages V-VI pathology compared with those modestly affected (stages I-II). Conversely, the level of plasmalogens, which need intact peroxisomes for their biosynthesis, was decreased in severely affected tissues, in agreement with a peroxisomal dysfunction. In addition, the peroxisomal volume density was increased in the soma of neurons in gyrus frontalis at advanced AD stages. Confocal laser microscopy demonstrated a loss of peroxisomes in neuronal processes with abnormally phosphorylated tau protein, implicating impaired trafficking as the cause of altered peroxisomal distribution. Besides the original Braak staging, the study design allowed a direct correlation between the biochemical findings and the amount of neurofibrillary tangles (NFT) and neuritic plaques, quantified in adjacent tissue sections. Interestingly, the decrease in plasmalogens and the increase in VLCFA and peroxisomal volume density in neuronal somata all showed a stronger association with NFT than with neuritic plaques. These results indicate substantial peroxisome-related alterations in AD, which may contribute to the progression of AD pathology.